Introducing digital technologies in person-related services—Support through Social Service Engineering - Anne Steputat-Rätze; Kristin Gilbert; Ulrike Pietrzyk; Romy Wöhlert (Zeitschrift für Arbeitswissenschaft, 2023)
The trend towards digitalization has made its way into personal services, promising better service quality for customers and improved working conditions for service providers. However, the implementation of digital technologies remains a~major challenge, especially for smaller companies. Building on the results of the SO-SERVE project, this paper presents the concept of Social Service Engineering and its practical application in introducing a~digital tool in two daycare centers. The software provided to the employees on tablets was intended to support the information and documentation processes, as the design of internal and external information flows and documentation processes in the daycare centers proved to be particularly challenging. The paper presents two exemplary SO-SERVE tools used in the daycare centers: 'Digitization Checklists' provide company managers and business unit managers with an overview of the necessary steps for the standardized use of software and hardware within the company. 'Digitization companions' are employees who are readily available to their colleagues as contact persons for questions and concerns about working with the new digital tool. An initial online evaluation with 23~educators from the daycare centers reveals that the digital tool and supporting SO-SERVE tools have improved information and documentation processes, and the work situation of employees. Both educators and parents benefit from the improvements.
Keywords: 650; Digitization; Software introduction; Work design; Childcare; Digitalisierung; Einführung neuer Software; Arbeitsgestaltung; Kinderbetreuung